Exploring Interpersonal Networks Based on Text Analysis: Insights from the Overseas Taiwanese Leftist Databas - Yi-Chieh Wu; Hua-Yuan Hsueh (Tūzī yǔ dàng’àn xuékān, 2024)
This study utilizes the digital archives of the “Taiwan Sitai,” led by the leftist movement leader Tso Hsiung. The database comprises 498 documents totaling 2.29 million words, including magazines, internal newsletters, and member correspondence, spanning from 1970 to 2018. Through advanced natural language processing techniques such as named entity recognition (NER) and keyword extraction (key terms), we analyzed the social network dynamics among members. The findings are illustrated with dynamic data visualizations that provide comprehensive network graphs, capturing diverse relationships and facets. Such visualizations serve as convenient tools to assist qualitative and quantitative research in social sciences.